2018
DOI: 10.18632/oncotarget.24643
|View full text |Cite
|
Sign up to set email alerts
|

Pro-tumoral immune cell alterations in wild type and Shb-deficient mice in response to 4T1 breast carcinomas

Abstract: To assess mechanisms responsible for breast carcinoma metastasis, 4T1 breast carcinomas were grown orthotopically in wild type or Shb knockout mice. Tumor growth, metastasis, vascular characteristics and immune cell properties were analyzed. Absence of Shb did not affect tumor growth although it increased lung metastasis. Shb knockout mouse tumors showed decreased redness and less developed vascular plexa located at the periphery of the tumors. No difference in overall tumor vascular density, leakage or pericy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 47 publications
0
16
0
Order By: Relevance
“…The cross presentation by DCs play an important role to further activate T cells in autoimmune diseases and cancer . Cross‐presenting DCs can be further characterized by using a CD8α marker together with DCs markers such as CD11b and CD11c.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The cross presentation by DCs play an important role to further activate T cells in autoimmune diseases and cancer . Cross‐presenting DCs can be further characterized by using a CD8α marker together with DCs markers such as CD11b and CD11c.…”
Section: Resultsmentioning
confidence: 99%
“…The cross presentation by DCs play an important role to further activate T cells in autoimmune diseases 37,38 and cancer. 39,40 Cross-presenting DCs can be further characterized Vehicle MLDSTZ by using a CD8α marker together with DCs markers such as CD11b and CD11c. Therefore, we examined the proportion of CD11b + CD11c − CD8 + , CD11b − CD11c + CD8 + , and CD11b + CD11c + CD8 + DCs.…”
Section: Proportions Of Cd8 + Dcs Are Increased In Mldstz-treated Micementioning
confidence: 99%
“…This cytokine is a novel anti‐inflammatory cytokine, which belongs to the IL‐12 cytokine family, and has two subunits, Ebi3 and IL‐12p35 . It has previously been reported that IL‐35 suppresses autoimmunity and plays a putative role in tumour biology . We have found that the systemic administration of IL‐35 prevented the development of autoimmune diabetes in the multiple low‐dose streptozotocin (MLDSTZ) mouse model, and effectively reversed established disease in both the MLDSTZ and non‐obese diabetic mouse models of T1D by maintaining the normal suppressive phenotype of T reg cells .…”
Section: Introductionmentioning
confidence: 92%
“…Thymi, spleens, inguinal lymph nodes, bone marrows and blood were collected and cells isolated that were stained for CD4 and FoxP3 and analyzed by fluorescence activated cell sorting (FACS) as described 5 .…”
Section: Methodsmentioning
confidence: 99%